EVALUATION OF THE ACTIVITY OF GIVING READY-TO-USE THERAPEUTIC FOOD PLUMPY NUTS TO MALNOURISHED CHILDREN IN TANGERANG CITY - Amir, Chindy; Susetyowati, Susetyowati; Arjuna, Tony (International Journal of Multidisciplinary Research and Literature, 2024)
Background: RUTF is a high-energy lipid-based food used for the treatment of Severe Acute Malnutrition (SAM) children. RUTF is given to SAM children under five years old who are entering the rehabilitation and outpatient phase at the public health centre. RUTF plumpy nut (eeZeePaste) as a nutrition intervention for treatment SAM in Tangerang City. The implementation provision of RUTF has been going on for one year in Tangerang City. but in practice there are variations in its use. Objective: This study aim to evaluation of provision RUTF plumpy nut to SAM children in Tangerang City. Methods: A qualitative study with a case study approach aim to  evaluation of provision RUTF plumpy nut to SAM children in Tangerang City. Results: The provision of RUTF Plumpy Nut in Kota Tangerang has not been well implemented. There is no specific SOP regarding the provision of RUTF Plumpy Nut, which has led to the suboptimal provision of RUTF Plumpy Nut. RUTF Plumpy Nut is not ideally given to malnourished children in Tangerang City because the RUTF Plumpy Nut given to malnourished toddlers is not well received in terms of taste, portion size and ingredients that are not in accordance with the habits and tastes of children in the Tangerang City area. Conclusion: The provision of RUTF Plumpy Nut to malnourished children has not gone well and malnourished children in Tangerang City don’t like RUTF Plumpy Nut